Clothing Terminology in Sveta Trojica in Pleteršnik’s Dictionary - Koletnik, Mihaela (ZORA 160: Imenitnost slovenščine sto let po Pleteršniku, 2026)
The paper discusses the dialectal names of clothing in the Sveta Trojica local dialect belonging to the Slovenske gorice dialect, which, in turn, is part of the Pannonian dialectal group. The collected dialectal terms are compared with the entries found in Pleteršnik’s Slovene-German Dictionary (1894–95) in order to shed light on the history of the occurrence of the individual words, the scope and the frequency of their occurrence and the possible semantic differences. We are also interested in the key according to which the dialectal clothing terminology is presented in Pleteršnik’s dictionary.